Supramolecular scaffolds on glass slides as sugar based rewritable sensors for bacteria - Gade, Madhuri; Paul, Ajay; Alex, Catherine; Choudhury, Devika; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemical Communications, 2015)
We describe here the sugar functionalized beta-cyclodextrin-ferrocene glass slides as fully reversible bacterial biosensors under the influence of external adamantane carboxylic acid. The prototype D-mannose - E. coli ORN 178 and L-fucose - P. aeruginosa interactions serve as a model to illustrate the new approach.